2019
DOI: 10.5513/jcea01/20.1.2052
|View full text |Cite
|
Sign up to set email alerts
|

European corn borer and its parasites overwintering abundance and damages on different corn FAO maturity groups

Abstract: European corn borer (ECB) is one of the most significant maize pests in the world and also in Croatia. ECB causes yield reduction from 2 to 25%, even more in years favorable for its development. According to estimations, these losses are around 7%. About 90% of the hybrids had some resistance to whorl-leaf feeding (first-generation ECB) and 75% had some resistance to sheath and sheath-collar feeding (secondgeneration ECB). Along with resistance, modern maize hybrids possess certain level of tolerance. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…For example, Patch [ 35 ] reported that the height of maize or a factor, such as maturity correlated with height, was the main factor in the selection of maize by the ECB moths for oviposition. Maize hybrids planted earlier and the hybrids with extensive vegetative growth were attractive to moths to lay eggs, and therefore those hybrids suffered higher infestation from first generation ECB [ 25 , 32 ]. Recent investigations conducted by Leppik and Frérot [ 36 ] reported on maize odorscapes under field conditions that may improve host plant detection in ECB moths during oviposition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Patch [ 35 ] reported that the height of maize or a factor, such as maturity correlated with height, was the main factor in the selection of maize by the ECB moths for oviposition. Maize hybrids planted earlier and the hybrids with extensive vegetative growth were attractive to moths to lay eggs, and therefore those hybrids suffered higher infestation from first generation ECB [ 25 , 32 ]. Recent investigations conducted by Leppik and Frérot [ 36 ] reported on maize odorscapes under field conditions that may improve host plant detection in ECB moths during oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…The results with Croatian hybrids and their tolerance to ECB reported by Ivezić and Raspudić [ 15 ], Lemić et al [ 25 ] and Augustinović et al [ 33 ] were based either on smaller number of hybrids or on the few locations included in the investigation. The lack of correlation between the FAO maturity group and the percent of infestation obtained in our study was in line with the data reported by Augustinović et al [ 33 ], who reported significant differences in the intensity of the damaging effects on different locations and no significant differences concerning various hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations